Modelling and simulation of cyclic nanoindentation for Y-TZP ceramic / S. K. H. Baharudin and J. Saedon - Baharudin, S. K. H.; Saedon, J. (Smart Manufacturing Research Institute (SMRI), 2024)
Cyclic nanoindentation is a robust experimental method that enables an in-depth analysis of how materials behave mechanically under repeated loading conditions. The aim of this study is to utilize the cyclic nanoindentation technique in order to assess the mechanical characteristics, including elastic and plastic deformations, of yttriastabilized tetragonal zirconia polycrystals (Y-TZP) ceramic material through simulation. A two dimensional Finite Element Analysis (FEA) model is employed to create a nanoindentation simulation with a Berkovich indenter. The cyclic nanoindentation simulation model provides the outcome of the sample's deformation response and the load-displacement curve for each loading cycle of peak load of 500 mN. This model builds upon our previous research with Saedon et al., where we successfully replicated the load-displacement curve obtained by earlier researchers through a single nanoindentation simulation. Given that the sample model is reliable, the results achieved with Y-TZP ceramic are also depandable. In conclusion, this research has successfully replicated the cyclic nanoindentation method using a Berkovich indenter simulation to analyse and understand the mechanical characteristics of Y-TZP ceramic, which is commonly employed in dental prosthetics.